The Contribution of Problem-Solving Ability To Self-Regulated Learning of Khairul Imam Medan Middle School Students - Sari, Nilam; Heryanto, Heryanto; Peranginangin, Lorena; Tobing, Renatal Halomoan Lumban (Universitas Wiralodra, 2024)
The purpose of this study is to ascertain the contribution of mathematical problem-solving abilities to self-regulated learning. This research is ex post facto research. The sample taken in this study using the cluster random sampling technique was taken randomly from two classes with a total of 51 students. Data on problem-solving abilities and self-regulated learning were collected using instruments in the form of problem-solving ability tests and self-regulated learning attitude scales. Path analysis techniques were used to analyze the data. The results of the research show that problem-solving abilities contribute significantly to students' self-regulated learning, and the large contribution of problem-solving abilities to students' self-regulated learning is 94.47%. Based on these findings, it can be concluded that to increase student self-regulated learning, problem-solving abilities must be improved. Apart from that, problem-solving abilities contribute significantly to self-regulated learning, both directly and indirectly, and these two variables have a very strong influence.